Nitrogen enrichment enhances the negative top–down effect on plant functional traits - Zhang, Dongmei; Zhang, Liwen; Lan, Siqun; Zhao, Lianjun; Han, Guangxuan; Chen, Lin (Frontiers in Plant Science, 2024)
Eutrophication resulting from anthropogenic activities has been recognized as a significantly drivers of changes in ecosystem functioning. Furthermore, it may exacerbate the top-down effect and thus exert an important impact on plant growth. To test this hypothesis, we conducted a three-year manipulative field experiment to investigate the impacts of nitrogen addition and crab herbivory on the growth of Phragmites australis in the salt marsh of the Yellow River Delta.The results demonstrated that a three-year of nitrogen addition can significantly increase the total nitrogen and carbon content of P. australis leaves, thereby enhancing their nutritional value and palatability, as well as increasing the proportion of leaves consumed by crabs. Therefore, nitrogen addition together with crab herbivory had a significant negative effect on P. australis height, leaf length, and leaf breadth in the Ambient Crab and Procedural Crab Cage Treatment compared to the Crab Exclusion Treatment. The structural equation modeling further substantiated these findings. The model revealed a direct and positive correlation between nitrogen addition and leaf nutrient content (path coefficient = 0.34). Additionally, it demonstrated a direct and positive relationship between leaf nutrient content and the proportion of leaves consumed by crabs (path coefficient = 0.22). Simultaneously, there was an observed negative correlation (path coefficient = -0.37) between the proportion of leaves consumed by crabs and plant functional traits, represented by leaf length in the model, during 2018. Moreover, the Crab Exclusion treatment significantly reduced the proportion of leaves consumed by crabs, and thus enhanced the P. australis individuals, leaf number and biomass. Overall, crab herbivory had significant detrimental top-down effect on the growth of P. australis, and nitrogen enrichment may exacerbate this topdown effect.The findings of our study highlight the combined adverse effects of nutrient enrichment and top-down on plant functional traits and plant growth. The findings of this study will contribute to a comprehensive understanding of the underlying factors influencing vegetation degradation in the coastal wetland, thereby establishing a solid theoretical framework for the conservation and management of wetland ecosystems within the context of global environmental change.